GROUNDED THEORY ANALYSIS OF THE IMPACT OF ORGANIZATIONAL CULTURE ON EMPLOYEE ACHIEVEMENT - Munizu, Musran; Amir , Arfenti; Mas’ud, Marwah; Syafri, Muhammad (PT. Altin Riset Publishing, 2023)
The aim of this research is to understand how organizational culture influences employee performance, which is very important in creating a positive work environment and increasing overall organizational effectiveness. This research involved collecting qualitative data through interviews, observations, and document analysis. A diverse sample from various levels and departments within the organization will be selected to ensure a comprehensive understanding of cultural dynamics and their impact on employee performance. Through an iterative process of data collection and analysis, this research aims to develop a theoretical framework that explains the relationship between organizational culture and employee performance. This framework will provide insight into specific cultural elements, such as values, norms, communication patterns, and leadership styles, that influence employee behavior and ultimately influence their performance outcomes. The findings of this research will contribute to theoretical and practical knowledge. Theoretically, this research will increase our understanding of the complex interactions between organizational culture and employee performance. Practically, the findings of this research can inform organizations about the importance of developing a positive and supportive culture that is aligned with desired performance outcomes. This knowledge can guide organizations in designing effective interventions, such as training programs, leadership development initiatives, and communications strategies, to establish a culture that maximizes employee performance and organizational success.